AB0936 A NATIONAL SURVEY OF CLINICAL PRACTICE OF CORTICOSTEROID USE IN NEWLY DIAGNOSED OR FLARING CASES OF JUVENILE IDIOPATHIC ARTHRITIS ACROSS THE UK. (June 2019) - Baildam, Eileen; Jones, Ashley; Clayton, Dannii; Nkoma, Gloria; Peak, Matthew; Ramanan, Athimalaipet; Rooney, Madeleine; Foster, Helen; Stones, Simon; Mcerlane, Flora; Moitt, Tracy; Roper, Louise; et al.
Abstract : Background: Corticosteroids (CS) are widely used for rapid-action or induction treatment in children and young people (CYP) with juvenile idiopathic arthritis (JIA). Given a lack of evidence base on CS induction regimen for CYP with JIA, and since criteria for choosing CS are based on healthcare professional (HCP) preference, further research is needed (1). Objectives: To establish the opinions of HCPs current practice regarding the clinical criteria for commencing CS treatment Methods: A national electronic survey was undertaken among HCPs across the UK as part of the Steroid Induction Regimen for Juvenile Idiopathic Arthritis (SIRJIA) study. Results: A total of 39 (24%) responses were received from 162 HCPs. These included 22 (56%) NHS consultants, five (13%) grid trainees, eight (21%) clinical nurse specialists and four other HCPs (10%). The most common treatments in CYPs with newly diagnosed JIA or a disease flare were intra-articular (IA) CS or a combination of DMARDs and IAS (except for systemic JIA and oligoarticular JIA). The majority of HCPs 17 would treat new and flaring CYP the same in terms of a CS remission induction regime, with 53% choosing a different regime or not answering. The key criteria that HCPs used for commencing CS and choosing the route of administration were rapid induction of remission (31 (89%)), high disease activity (31 (89%)), severity of systemic JIA (30 (86%)) and level of inflammation (28 (80%)) Table 1 . The number one determinant of route of administration of CS was disease severity followed by disease subtype. The majority of HCPs (52-72% depending on role) would consider entering CYP with JIA into a trial randomising to the various modes of administration. Table 1: Conclusion: The results from this national survey of clinical practice showed varying practices in the management of new CYP with JIA and those that are flaring. The majority of HCPs who completed this survey, indicated that they would be prepared to consider entering CYP into a trial that randomised to the four CS delivery methods. References: [1] Deepak, et al. 2017Literature review on the use of corticosteroids in juvenile idiopathic arthritis (JIA) Rheumatology56(Suppl7) Acknowledgement: This study was funded by the NIHR Health Technology Assessment Programme (14/167/01). The funders did not have a role in the design, collection, analysis, or interpretation of the data Disclosure of Interests: Eileen Baildam Consultant for: EB has received one paid consultancy for Pfizer in the last 12 months, but this was not related to this study., Ashley Jones: None declared, Dannii Clayton: None declared, Gloria Nkoma: None declared, Matthew Peak: None declared, Athimalaipet Ramanan Consultant for: AbbVie, UCB, Sobi, Eli Lilly, Speakers bureau: Speaker fees/honoraria from Abbvie, SOBI, Eli Lilly and UCB, Speakers bureau: AbbVie, UCB, Sobi, Eli Lilly, Madeleine Rooney: None declared, Helen Foster: None declared, Simon Stones Consultant for: SS has provided consultancy services to Envision Pharma Group, though this is not related to the contents of this abstract., Speakers bureau: SS has undertaken speaking engagements for Actelion, eyeforpharma, Four Health, Janssen and Roche, though these are not related to the contents of this abstract., Flora McErlane: None declared, Tracy Moitt: None declared, Louise Roper: None declared, Bridget Young: None declared, Frances Sherratt: None declared, Michael Beresford: None declared